2016
DOI: 10.2169/internalmedicine.55.5764
|View full text |Cite
|
Sign up to set email alerts
|

Multimarker Prognostication for Hospitalized Patients with Community-acquired Pneumonia

Abstract: Objective The optimal prognostic model for community-acquired pneumonia (CAP) remains unclear. In this study, we sought to identify independent predictors of 30-day mortality in patients with CAP and to determine whether adding specific prognostic factors to each of the two clinical prediction scores could improve the prognostic yield. Methods This retrospective study involved 797 CAP patients who had been hospitalized at a tertiary referral center. The patients were categorized into two groups: those who surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Studies from Japan and Korea showed that serum albumin is not less accurate than CURB-65 or PSI class for predicting 30-day mortality in CAP patients. 26,27 In this study, hypoalbuminemia was closely correlated with in-hospital mortality of CAP in T2DM patients. Compared to T2DM patients with albumin ≥35 g/L, T2DM patients with albumin 25-34.9 g/L [OR= 4.929] and albumin <25 g/L [OR= 12.463] were more likely to die at the time of hospitalization.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Studies from Japan and Korea showed that serum albumin is not less accurate than CURB-65 or PSI class for predicting 30-day mortality in CAP patients. 26,27 In this study, hypoalbuminemia was closely correlated with in-hospital mortality of CAP in T2DM patients. Compared to T2DM patients with albumin ≥35 g/L, T2DM patients with albumin 25-34.9 g/L [OR= 4.929] and albumin <25 g/L [OR= 12.463] were more likely to die at the time of hospitalization.…”
Section: Discussionmentioning
confidence: 50%
“…Some studies have proven that hypoalbuminemia significantly improved the performance of CURB-65 and PSI class for predicting mortality in patients with CAP. 17 , 26 , 34 , 35 However, CURB-65 and PSI class, particularly PSI class, are complicated scoring systems. Serum albumin makes the systems more complex.…”
Section: Discussionmentioning
confidence: 99%
“…There is believed to be a link between malnutrition and inflammation, and hypoalbuminemia has been noted as an inflammatory marker associated with increased risk of poor clinical outcome [14]. Hypoalbuminemia can lead to weakened immunity and increased susceptibility to infectious diseases, and patients with sepsis have complex pathophysiological conditions, including immune imbalance and disorders of biosynthesis and catabolism [15]. Furthermore, hypoalbuminemia was found to be an independent predictor of fatal sepsis in an intensive care unit, with a 75.2% increase in the mortality rate among patients with serum albumin <2.9 g/dL [16].…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, for the assessment of prognosis of patients with community-acquired pneumonia, combined use of CURB-65 and PCT, [7–9,11,16,18,19] and combined use of CURB-65 and Alb, [6,10,12–14,21,27] have been widely applied. Alb is known to be a prognostic factor for elderly people.…”
Section: Discussionmentioning
confidence: 99%